Influência do cultivo de mexilhões sobre o habitat bentônico na Enseada da Armação do Itapocoroy, Penha, SC - Marenzi, Adriano Weidner Cacciatori (2002)
Mussel culture is an important activity in the state of Santa Catarina, where is developed in almost all the bays and roadsteads. This activity places the state in evidence in Latin America s production. However, this development has been spread in a disorganized way, generating environmental impacts, mainly those arisen from bio deposition of organic material at cultivation areas. The main purpose of this research was to evaluate a roadstead under cultivating influences, determining changes in sediment and benthic macro invertebrate s communities. Three sampling points were chosen according to activity time and intensity. Therefore, the level of organic material in the sediment, the structure and composition of the benthic community were accessed. Results showed that sand was the main material in sediment and rough particles are predominant near the shore side. The carbonate, silt and gravel levels were high at intense cultivating areas. However, differences concerning organic materials were not observed between cultivated and non-cultivated areas. The fauna collected was represented by 65 species belonging to 7 phyla, being the ophiurans more frequently found in the samples. Even though there were no meaningful differences between time and place for picking up samples, higher density and abundance occurred during winter and fall within non-cultivated areas, where debris eater s mollusks are highlighted. Higher richness and diversity were detected during winter and summer time in intensively cultivated areas, with great participation of polychaeta species. Results showed that mussel cultures are not causing direct impacts once the wind action promotes a situation of high hydrodynamics in the region and is a determinative factor in sediment constitution and benthic fauna.